Effect of Modular Intervention on Eighth-Grade Students’ Algebraic Reasoning: A Quasi-Experimental Study - Chaurasia, Prateek; Singh, Somu (JOURNAL OF INDIAN EDUCATION, 2026)
The present study is a quasi-experimental investigation of the effect of a self-developed module on algebraic reasoning among eighth-grade students to improve their algebra learning. The participants were students from both public and private schools within the same district. To test the effectiveness of the module, four schools were selected—two assigned as experimental groups and two as control groups. Students in the experimental groups received modular teaching, while students in the control groups received traditional teaching. The findings were significant and provide valuable insights for classroom teachers and other stakeholders regarding the enhancement of algebraic learning. The results suggest that the module on algebraic reasoning was significantly effective in improving both algebraic reasoning and algebra achievement. It is recommended that the integration of substantial algebraic reasoning activities can have a positive impact on students’ algebraic understanding and, more broadly, on mathematics learning at the middle-school level